2006
DOI: 10.1088/0022-3727/39/5/s10
|View full text |Cite
|
Sign up to set email alerts
|

X-ray resonant magnetic scattering study of [Co2MnGe/Au]nand [Co2MnGe/V]nmultilayers

Abstract: Abstract. We study the structure and magnetism of the ferromagnetic half metallic Heusler compound Co 2 MnGe in high-quality [Co 2 MnGe/Au] n -and [Co 2 MnGe/V] n -multilayers by hard x-ray scattering and soft x-ray resonant magnetic scattering (XRMS). The diffuse hard x-ray scattering reveals that in [Co 2 MnGe/Au] n at the interfaces correlated roughness dominates and interdiffusion is negligible, whereas in [Co 2 MnGe/V] n the roughness is uncorrelated and dominated by interdiffusion. An analysis of energy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Typically, this technique is performed by analyzing the energy dependence of the reflectivity at different angular or scattering vector values, [3][4][5][6][7][8] whereas recently strong interest has emerged in the analysis of the angular dependence of the reflectivity close to an absorption edge. [9][10][11][12][13] This turns out to be particularly relevant in the soft x-ray range where the reflectivity measured at large scattering angles is sensitive to out-of-plane magnetization.…”
mentioning
confidence: 99%
“…Typically, this technique is performed by analyzing the energy dependence of the reflectivity at different angular or scattering vector values, [3][4][5][6][7][8] whereas recently strong interest has emerged in the analysis of the angular dependence of the reflectivity close to an absorption edge. [9][10][11][12][13] This turns out to be particularly relevant in the soft x-ray range where the reflectivity measured at large scattering angles is sensitive to out-of-plane magnetization.…”
mentioning
confidence: 99%
“…However, high temperature annealing often leads to interdiffusion and local changes of the stoichiometry in Heusler compounds [13]. For FePt thin layers, however, it has been demonstrated that the degree of chemical order can alternatively be controlled by post-growth irradiation with He + ions [14,15].…”
mentioning
confidence: 99%
“…Different models can be used for the form factor depending on the film structure. When the mixing of atoms at the interfaces is absent, the quantity ∆ k for the bilayer can be represented in the framework of the step model: (6) where θ(z) is the Heaviside theta function and C a and C b are constants. In the framework of this model, the permittivities in each metal layer are constant and change abruptly upon changing over to the metal of another type.…”
Section: X-ray Scattering From Multilayer Systemsmentioning
confidence: 99%
“…In particular, it has become possible to analyze not only static properties but also dynamic properties of nanostructures on the atomic level by measuring the time correlation functions of the x-ray intensity [2][3][4]. Moreover, the use of polarized x-ray radiation has made it possible to investigate magnetic properties [5,6].…”
Section: Introductionmentioning
confidence: 99%